Cyclophilin D Contributes to Anesthesia Neurotoxicity in the Developing Brain - Zhang, Yiying; Lu, Pan; Liang, Feng; Liufu, Ning; Dong, Yuanlin; Zheng, Jialin Charles; Xie, Zhongcong (Frontiers in Cell and Developmental Biology, 2020)
Anesthetic sevoflurane induces mitochondrial dysfunction, impairment of neurogenesis, and cognitive impairment in young mice, but the underlying mechanism remains to be determined. Cyclophilin D (CypD) is a modulatory factor for the mitochondrial permeability transition pore (mPTP). We, therefore, set out to evaluate the role of CypD in these sevoflurane-induced changes in vitro and in young mice. WT and CypD knockout (KO) young (postnatal day 6, 7 and 8) mice received 3% sevoflurane two hours daily, and neural progenitor cells (NPCs) harvested from the WT or CypD KO mice received 4.1% sevoflurane. Mass spectrometry was used to identify the targeted protein(s) of sevoflurane action in the harvested hippocampus tissues of the wild-type (WT) young mice. We then used immunohistochemistry and immunocytochemistry imaging, flow cytometry, Western blot, RT-PCR, co-immunoprecipitation and Morris Water Maze to assess the interaction of sevoflurane and CypD on mitochondria function, neurogenesis, and cognition in vitro and in WT or CypD KO mice. In the present studies, we first identified CypD as the target protein of sevoflurane action. We demonstrated that the sevoflurane anesthesia induced accumulation of CypD, mitochondrial dysfunction, impairment of neurogenesis, and cognitive impairment in WT young mice or NPCs harvested from WT mice, but not in CypD KO mice or NPCs harvested from CypD KO mice. Finally, the sevoflurane anesthesia reduced binding of CypD with ANT, the other component of mPTP. These data suggest that the sevoflurane anesthesia might induce a CypD-dependent mitochondria dysfunction, impairment of neurogenesis, and cognitive impairment in young mice and NPCs.